Openbite etiology, morphology and treatment considerations - Moldez, Marlon A.
Openbite in a young patient is amenable to wider range of management possibilities: simple habit control, growth modification, and orthodontic treatment. But a full-blown skeletal openbite is difficult to treat and and refractory to orthodontic approach alone. The vast majority of adults with skeletal openbite require a combined orthodontic-surgical approach to ensure positive improvement of oral functions and facial aesthetics. In modern orthodontics, treatment is initiated only if all the underlying variables are fully understood and evaluated.
Keywords: Dental openbite; Skeletal openbite; Vertical disproportions